Establishment of a reference material for standardization of the anti-complementary activity test in intravenous immunoglobulin products used in Japan: A collaborative study - Nojima, Kiyoko; Okuma, Kazu; Ochiai, Masaki; Kuramitsu, Madoka; Tezuka, Kenta; Ishii, Mieko; Ueda, Sadao; Miyamoto, Takashi; Kamimura, Koichiro; Kou, Enki; Uchida, Sanae; Watanabe, Yoshiharu; et al. (Biologicals, 2017)
Aggregates of human plasma-derived intravenous immunoglobulins (IVIGs) carries a risk of severe adverse events after nonspecific complement activation induced in humans administrated. Therefore, the anti-complementary activity (ACA) test is legally required in every batch of IVIGs in Japan. However, due to the intrinsic nature of this bioassay, there might be large differences in the results of ACA tests from laboratories, even when the same batch of IVIGs was measured. Our six laboratories evaluated whether there were such differences and argued for establishment of a reference material (RM) for standardization of the ACA test. Our results revealed inter-laboratory differences in ACA values, indicating a need to establish an RM. Therefore, after ACA values in candidate RMs were measured collaboratively, one RM was selected from two candidates and unit value-assigned. The RM in fact normalized the ACA test values for samples measured in parallel at almost all the laboratories, when the values were calculated relative to the assigned unit value of the RM. Thus, we established a first RM to standardize the ACA test in Japan, which enabled each laboratory to normalize ACA values constantly for IVIGs. This indicates that the establishment of an RM can contribute to quality control of IVIGs.